High speed impact properties of carbon-basalt-flax DHEC composites compared with pure carbon fibre composites. (15th May 2018) - Nisini, E.; Santulli, C.; Ceruti, A.; Liverani, A.
Abstract: A new composite material, defined as Ductile High Energy Composite (DHEC), is analysed in this paper, with particular reference to the energy absorbed after high speed impacts and to the relevant failure mode. A set of DHEC and pure carbon fibre laminates presenting equal weight, equal bending strength or equal stiffness, respectively, have been compared measuring the energy absorbed after the impact of a bullet, through the difference between the total energy of the bullet and the one corresponding to its penetration in a wooden block after hitting the specimens. Fracture modes have been investigated using an optical microscope. Energy absorbed by DHEC laminates is of the same order than for pure carbon ones; however, the DHEC failure mode (referred to as "petaling") presents a lower spreading of splinters respect to the pure carbon fibres (brittle fracture) case. Even though a wider testing campaign is necessary to better evaluate the DHEC properties, they appear to be suitable for adoption in all those applications where impacts can be harmful for end-users or people. Further research on high energy absorption properties is needed to better characterize these innovative composite materials, yet the outcome of this study suggests the high potential of DHEC.